AC4 protein of tomato leaf curl Palampur virus is an RNA silencing suppressor and a pathogenicity determinant. (October 2019) - Kulshreshtha, Aditya; Kumar, Yogesh; Roshan, Poonam; Bhattacharjee, Bipasha; Mukherjee, Sunil Kumar; Hallan, Vipin
Abstract: Plants deploy RNA silencing as a natural defence against invading viruses involving sequence-specific degradation of the viral RNAs. As a counter-defence strategy, viruses encode suppressor proteins that simultaneously target different steps of the silencing machinery. Tomato leaf curl Palampur virus (ToLCPalV) is a bipartite begomovirus in Geminiviridae family. It is responsible for significant reduction in the crop yield and quality. DNA-A of the virus encodes for six proteins whereas DNA-B codes for two proteins. In this study, all viral genes were screened for their role in suppression of green fluorescent protein (GFP) silencing in Nicotiana tabacum cv. Xanthi, employing agrobacterium based co-infiltration assay. The assay identified AC4 as a potential suppressor of RNA silencing. In addition, AC4 expression also suppressed virus-induced gene silencing (VIGS) of the phytoene desaturase (PDS) gene in N. benthamiana . Potato virus X (PVX) mediated transient expression of the AC4 in N. benthamiana showed enhanced symptoms that include downward leaf curling, leaf puckering and tissue necrosis. Further, N. benthamiana lines stably expressing AC4 showed severe developmental abnormalities. Mutational analysis suggested that glycine at 2 nd position is essential for AC4 pathogenicity. Collectively, these findings demonstrate the role of ToLCPalV AC4 in viral pathogenesis, disease establishment and suppression of gene silencing. Graphical abstract: Image 1